The interests of South Africa as BRIC - Morasso, Carla Maria (2013)
The aim of this paper is to examine the initiatives developed by the government of South Africa to be part of the BRIC (Brazil, Russia, India and China) and identify their interests in the group. South Africa intends to strengthen its role as a regional power in Africa and, at the same time, it wants to have the status of an emerging country. The external policy of South Africa lies in a new phase of challenges from the consolidation of itself as an average power, and if it is added to the group, it can contribute to goals in the current international scenario.